1993
DOI: 10.1084/jem.178.6.2157
|View full text |Cite
|
Sign up to set email alerts
|

Expression and catalytic activity of the tyrosine phosphatase PTP1C is severely impaired in motheaten and viable motheaten mice.

Abstract: SummaryMutations in the gene encoding the phosphotyrosine phosphatase PTP1C, a cytoplasmic protein containing a C0014-terminal catalytic and two NH2-terminal Src homology 2 (SH2) domains, have been identified in motheaten (me) and viable motheaten (me) mice and are associated with severe hemopoietic dysregulation. The me mutation is predicted to result in termination of the PTP1C polypeptide within the first SH2 domain, whereas the me°mutation creates an insertion or deletion in the phosphatase domain. No PTPI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
144
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(156 citation statements)
references
References 25 publications
10
144
0
2
Order By: Relevance
“…To specifically ascertain the biologic relevance of SHP-1 to the regulation of Src, activity of this PTK was next investigated in unstimulated thymocytes from motheaten (me) and viable motheaten (me v ) mice, animals that express negligible SHP-1 catalytic activity consequent to lossof-function mutations in the SHP-1 gene (30). As is consistent with previous data from our group (33), the results of anti-Src immunoblotting analysis confirmed the presence of Src in thymocytes from both mutant and normal, congenic mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To specifically ascertain the biologic relevance of SHP-1 to the regulation of Src, activity of this PTK was next investigated in unstimulated thymocytes from motheaten (me) and viable motheaten (me v ) mice, animals that express negligible SHP-1 catalytic activity consequent to lossof-function mutations in the SHP-1 gene (30). As is consistent with previous data from our group (33), the results of anti-Src immunoblotting analysis confirmed the presence of Src in thymocytes from both mutant and normal, congenic mice.…”
Section: Resultsmentioning
confidence: 99%
“…The SRC2 rabbit polyclonal anti-Src antibody, which recognizes a similar epitope as clone 28 and was demonstrated in comparative studies to also selectively immunoprecipitate the active form of Src (data not shown), was obtained from Santa Cruz Biotechnology (Santa Cruz, CA). Rabbit polyclonal anti-SHP-1 antibody recognizing the tandem SH2 domains of SHP-1 was generated in our laboratory as described previously (30). Rabbit anti-p56 lck antibody was produced in our laboratory by immunizing rabbits with a bacterial TrpE fusion protein containing amino acids 7-144 of Lck (31).…”
Section: Methodsmentioning
confidence: 99%
“…Northern blotting was conducted as described (16). Membranes were incubated with a-32 P ATP-labeled cDNA probes encoding either human SHP1 or 18S probe.…”
Section: Northern Blottingmentioning
confidence: 99%
“…How JNK activation induces inhibitory and antiproliferative signals in IGF-stimulated breast cancer cells remains unknown (13). To understand the antiproliferative activity of JNK in IGF-1-stimulated MCF-7 breast adenocarcinoma cells, we investigated the role of a well-studied SH-2 domaincontaining tyrosine phosphatase SHP1 whose activity has been associated with the termination of mitogenic cascades and signals activated by cytokines and antigens in hematopoietic cells (14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…To detect Shp-1 gene mutation, PCR-based genotyping was performed as previously described (38). All animal experiments were conducted according to the guideline of Tokyo Metropolitan Institute for Neuroscience.…”
Section: Micementioning
confidence: 99%